Low-angle phase boundary slip transfer and grain refinement enabling the simultaneous enhancement of strength-plasticity in fiber DP steel - Chuanlong Niu; Yilong Liang; Jiulou Long; Jinghua Yuan; Guigui Peng; Fei Liu; Xing Ran (Journal of Materials Research and Technology, 2025)
At present, the strength-plasticity of sorbite wire rods used for bridge cables is difficult to improve, and there is a serious lead pollution problem during the production process. To develop environmentally friendly materials with excellent strength-plasticity and work-hardening properties as a substitute for sorbite wire rods, an ultrafine crystalline fiber martensite/ferrite dual-phase (DP) steel with 63 % of low-angle phase boundary (LAPB) was fabricated by compoundly adding Mn, Ni, and Cu elements into a low-carbon alloy steel and combining with cyclic quenching. Research findings that LAPB not only facilitates the activation of identical slip systems in both phases but also enables a relatively high stress projection coefficient, which reaches 0.99, between these sliding systems. This higher stress projection efficiency, on the one hand, reduces the strain gradient of the initial martensite/ferrite, and on the other hand, promotes the deformation of martensite, enabling coordinated deformation and sustained work hardening. Furthermore, grain refinement introduces a high density of interfaces that impede dislocation motion while preventing localized deformation, thereby promoting dislocation-LAPB interactions. The synergistic effect of LAPB and grain refinement enables the strength-plasticity product to reach 16.3 GPa%, which is a 60 % improvement.